Recurrent Relatively Resistant Salmonella infantis Infection in 2 Immunocompromised Hosts Cleared With Prolonged Antibiotics and Fecal Microbiota Transplantation. (14th December 2018) - Torres Soto, Mariam; Hammond, Sarah; Elshaboury, Ramy H; Johnson, Jacob; Hohmann, Elizabeth L
Abstract: Two immunocompromised patients with relapsing gastrointestinal infection with relatively resistant Salmonella infantis were cured with prolonged ertapenem followed by encapsulated fecal transplant.